Klasifikasi Kopi Bubuk Spesialti Kalosi dan Toraja Menggunakan UV-Visible Spectroscopy dan Metode PLS-DA - Diding Suhandy; Meinilwita Yulia (Jurnal Ilmu Pertanian Indonesia, 2019)
Specialty coffee is sold in a very expensive price. Specialty coffee is usually consumed as a single origin (without mixed with other coffee). For this reason, the detection of impurities (authentication) in specialty coffee is a very important process to be performed. In this study, UV-visible spectroscopy combined with PLS-DA method were used to discriminate between two specialty coffees from South Sulawesi (Kalosi and Toraja). A number of 100 ground roasted coffee samples were used for Kalosi and Toraja, respectively (1 gram each sample). A standard aqueous extraction procedure of the coffee samples using distilled water was performed and the spectral data of aqueous samples of Kalosi and Toraja coffee were acquired in transmittance mode using a UV-Visible spectrometer (Genesys™ 10S UV-Vis, Thermo Scientific, USA). The result showed that using PLS-DA method, all prediction samples were correctly classified into their corresponding classes with 100% rate for sensitivity, specificity, and accuracy, respectively.